Feet at risk in the tennis player - Toffolo, M. (2001)
Ankle sprains are one of the most frequent injuries associated with sports. A recent study conducted among professional tennis players showeds that foot and ankle trauma are the 2nd main cause for tournament withdrawals and that 50% of all withdrawals account for trauma in the lower back and lower limb. One of the reasons for this lies in foot biomechanics. Not all ankle sprains can be avoided, but taking the biomechanical function of the foot into account can help to prevent injury. Altering foot function can reduce trauma and improve stability and muscle efficiency, which will in turn improve athletic performance. Athletes with certain types of feet are more prone to ankle sprains than others. Biomechanical analysis of foot function can determine those at risk and thus those that should be protected. There are two risk categories common to the tennis player: feet with excessive pronation and those with excessive supination. Both are described here (risks, effects, prevention, therapy).